Letter from Georg Bredig and Valeska Dombrowsky to Max Bredig, October 22, 1938 - Bredig, Georg; Dombrowsky, Valeska (1938)
Georg Bredig (1868-1944) gives professional advice to his son, Max Bredig (1902-1977) as he looks for a new position in the U.S.A and asks about his well-being. Additionally, Georg mentions the worsening conditions for Jewish citizens in Germany under the Third Reich. At the end of the letter, Georg’s sister, Valeska Dombrowsky (1871-1940), who is currently visiting Karlsruhe, sends warm regards to her nephew.
Keywords: Bredig, Georg, 1868-1944; Third Reich; Jewish Holocaust (1939-1945); Emigration and immigration; Jews, German